Infrared sensor using carbon nanotubes and its manufacturing method
By employing semiconducting carbon nanotubes with specific diameters and lengths, separated using a nonionic surfactant, the method addresses low TCR values in existing infrared sensors, enhancing performance and reducing costs for mass production and IoT compatibility.
Patent Information
- Application Number
- JP2023054703
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-29
- Filing Date
- 2023-03-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-01-17
AI Technical Summary
Existing infrared sensors using carbon nanotubes face challenges with low TCR values due to the presence of metallic carbon nanotubes and difficulties in removing ionic surfactants, limiting performance improvement.
A method involving the use of semiconducting carbon nanotubes with specific diameters and lengths, separated using a nonionic surfactant, to form a stable carbon nanotube network, allowing for high TCR values and enabling a printing process for mass production.
The method achieves an infrared sensor with enhanced TCR values and reduced manufacturing costs, suitable for applications in security surveillance, human body thermography, and vehicle-mounted cameras, while being compatible with IoT systems.
Smart Images

Figure 0007616262000001 
Figure 0007616262000002 
Figure 0007616262000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an infrared sensor using carbon nanotubes and a method for producing the same. [Background technology]
[0002] Infrared sensors have a very wide range of applications, including not only security cameras but also thermography of the human body, in-vehicle cameras, and inspection of structures and foods, and so in recent years, their industrial applications have been active. In particular, there is a demand for the development of inexpensive, high-performance infrared sensors that can obtain biometric information in conjunction with IoT (Internet of Things). In uncooled infrared sensors, VO x Vanadium oxide is currently used, but the process is expensive and the practical temperature coefficient of resistance (TCR) is small (approximately -2.0% / K), so there is a lot of research being done on improving the TCR.
[0003] To improve the TCR, a material with semiconducting properties and high carrier mobility is required, so it is expected that semiconducting single-walled carbon nanotubes with a large band gap and carrier mobility will be used in the bolometer section. However, single-walled carbon nanotubes usually contain carbon nanotubes with semiconducting properties and carbon nanotubes with metallic properties in a 2:1 ratio, so separation is necessary.
[0004] In Patent Document 1, a bolometer is proposed to be fabricated by applying a normal single-walled carbon nanotube to the bolometer portion, and taking advantage of the chemical stability of the single-walled carbon nanotube, mixing it with an organic solvent to prepare a dispersion liquid, which is then cast onto an electrode, in an inexpensive thin-film process. In this case, the single-walled carbon nanotube is annealed in air, which successfully improves the TCR to approximately -1.8% / K.
[0005] In Patent Document 2, since single-walled carbon nanotubes contain a mixture of metallic and semiconducting components, the researchers succeeded in achieving a TCR of -2.6% / K by extracting semiconducting single-walled carbon nanotubes with uniform chirality using an ionic surfactant and applying them to the bolometer section. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] WO2012 / 049801 issue [Patent Document 2] JP 2015-49207 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the carbon nanotube thin film used in the infrared sensor described in Patent Document 1, the carbon nanotubes are mixed with a large amount of metallic carbon nanotubes, so the TCR is low at room temperature, and there is a limit to improving the performance of the infrared sensor. Also, the infrared sensor using semiconducting carbon nanotubes described in Patent Document 2 has a problem in that the ionic surfactant used for separation cannot be easily removed.
[0008] In view of the above-mentioned problems, an object of the present invention is to provide an infrared sensor having a high TCR value using semiconducting carbon nanotubes, and a method for producing the same. [Means for solving the problem]
[0009] According to one aspect of the present invention, A substrate; a first electrode on the substrate; a second electrode on the substrate and spaced apart from the first electrode; a carbon nanotube layer electrically connected to the first electrode and the second electrode; Equipped with The carbon nanotube layer contains semiconducting carbon nanotubes at more than 66 mass% of the total amount of carbon nanotubes, and 60% or more of the carbon nanotubes contained in the carbon nanotube layer have a diameter in the range of 0.6 to 1.5 nm and a length in the range of 100 nm to 5 μm, thereby providing an infrared sensor.
[0010] According to another aspect of the present invention, A method for manufacturing an infrared sensor, comprising the steps of: The infrared sensor is A substrate; a first electrode on the substrate; a second electrode on the substrate and spaced apart from the first electrode; a carbon nanotube layer electrically connected to the first electrode and the second electrode; Equipped with A step of preparing a solution containing carbon nanotubes by mixing carbon nanotubes, a nonionic surfactant, and a dispersion medium; a step of dispersing and cutting the carbon nanotubes by subjecting the solution to a dispersion treatment to prepare a carbon nanotube dispersion; a step of subjecting the carbon nanotube dispersion to carrier-free electrophoresis to separate the semiconducting carbon nanotubes and the metallic carbon nanotubes, thereby preparing a semiconducting carbon nanotube dispersion containing the semiconducting carbon nanotubes; A step of connecting the first electrode and the second electrode with a carbon nanotube layer by the following sub-steps (a) to (c): (a) applying the semiconducting carbon nanotube dispersion onto a substrate; (b) a sub-step of heat-treating the substrate on which the semiconducting carbon nanotube dispersion liquid is applied; and (c) a sub-step of forming a first electrode and a second electrode on a substrate before the sub-step of applying the semiconducting carbon nanotube dispersion onto a substrate, or before or after the sub-step of heat-treating the substrate on which the semiconducting carbon nanotube dispersion has been applied. A method for manufacturing an infrared sensor is provided, comprising: Effect of the Invention
[0011] According to the present invention, it is possible to provide an infrared sensor having a high TCR value and a method for manufacturing the same. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram of an infrared sensor made according to the present invention. [Diagram 2] 1 is an atomic force microscope image of a semiconducting carbon nanotube film produced according to the present invention. [Diagram 3] FIG. 1 is a schematic diagram of a metal / semiconductor separation apparatus used in the present invention. [Figure 4] 1 is a graph showing the TCR values of an infrared sensor produced according to the present invention. [Diagram 5] 1 is a graph showing the TCR values of an infrared sensor produced according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have found that an infrared sensor having a high TCR value can be obtained by applying a semiconducting carbon nanotube having a specific diameter and length to the bolometer part. In addition, in one embodiment, the inventors have found that an infrared sensor having a high TCR value can be obtained by applying a semiconducting carbon nanotube separated by using a nonionic surfactant to the bolometer part. In one embodiment, the inventors have found that the TCR can be further improved by reducing the diameter of the semiconducting carbon nanotube.
[0014] Furthermore, in one embodiment, as described later, it is also preferable to use a nonionic surfactant with a long molecular length as the nonionic surfactant. Such a nonionic surfactant has a weak interaction with carbon nanotubes and can be easily removed after the dispersion is applied. Therefore, a stable carbon nanotube conductive network can be formed, and an excellent TCR value can be obtained. In addition, since such a nonionic surfactant has a long molecular length, the distance between the carbon nanotubes increases when the dispersion is applied, and they are less likely to re-aggregate when the electrode is prepared. Therefore, a carbon nanotube network in an isolated dispersion state can be formed while maintaining a moderate interval, and a large resistance change can be realized with respect to a temperature change. Furthermore, uniform application can be easily achieved by controlling the length of the carbon nanotubes. For the above reasons, the manufacturing method of the infrared sensor according to this embodiment is suitable for a printing process. Therefore, compared with the conventional method, the number of steps can be reduced because a printing process can be used, and there is also an advantage that the cost of sensor production can be reduced and mass productivity is excellent. In addition, in one embodiment, there is also an advantage that the cost can be reduced in that ultracentrifugation is not necessarily required in the separation process.
[0015] The present invention has the above-mentioned characteristics, and examples of the embodiments will be described below.
[0016] Fig. 1 is a schematic diagram of an infrared sensor detection section according to one embodiment of the present invention. A first electrode 2 and a second electrode 4 are provided on a substrate 1, and these electrodes are connected by a carbon nanotube layer 3 therebetween. As will be described later, this carbon nanotube layer 3 is mainly composed of a plurality of semiconducting carbon nanotubes separated using a nonionic surfactant. Such an infrared sensor can be manufactured, for example, as follows. A SiO 2 substrate is used. 2The silicon coated with the carbon nanotube is washed with acetone, isopropyl alcohol, and water in that order, and then the organic matter on the surface is removed by oxygen plasma treatment. The substrate is immersed in an aqueous solution of 3-aminopropyltriethoxysilane (APTES) and dried, after which a dispersion of semiconducting carbon nanotubes dispersed in a solution of polyoxyethylene alkyl ether such as polyoxyethylene (100) stearyl ether or polyoxyethylene (23) lauryl ether, which is a nonionic surfactant, is applied to the substrate and dried. The nonionic surfactant is removed by baking at 200°C in air. These operations form a thin layer of carbon nanotubes on the substrate. Then, first and second electrodes are fabricated by gold deposition, overlapping the thin layer of carbon nanotubes with a gap of 50 μm. An acrylic resin (PMMA) solution is applied to the area between the electrodes on the thin layer of carbon nanotubes formed to form a PMMA protective layer. After this, the entire substrate is subjected to oxygen plasma treatment to remove excess carbon nanotubes and the like in areas other than the carbon nanotube layer 3. Excess solvent and impurities are removed by heating at 200°C in air. The resulting infrared sensor detection unit in Figure 1 detects temperature by utilizing the temperature dependency of electrical resistance due to light irradiation. Therefore, it can be used in other frequency ranges as well if the temperature changes due to light irradiation, for example, the terahertz range can be detected. Furthermore, the change in electrical resistance due to temperature change can be detected not only by the structure in Figure 1, but also by amplifying the change in resistance value by providing a gate electrode to make it a field effect transistor.
[0017] Figure 2 shows an example of an atomic force microscope (AFM) image of carbon nanotubes on the substrate. The carbon nanotubes are almost isolated and dispersed, with a uniform diameter distribution, a network structure, and conductive paths.
[0018] In this specification, the term "carbon nanotube layer" refers to a layer made of a plurality of carbon nanotubes that form a conductive path that electrically connects a first electrode and a second electrode. The plurality of carbon nanotubes may form a structure such as parallel lines, fibers, or a network, but a network structure is preferred because it is less likely to aggregate and allows a uniform conductive path to be obtained. In this specification, the "carbon nanotube layer" may also be referred to as a "carbon nanotube film."
[0019] Carbon nanotubes may be single-walled, double-walled or multi-walled, but when separating a semiconductor type, single-walled or several-walled (e.g., two-walled or three-walled) carbon nanotubes are preferred, and single-walled carbon nanotubes are more preferred. Carbon nanotubes preferably contain 80% by mass or more of single-walled carbon nanotubes, and more preferably contain 90% by mass or more (including 100% by mass).
[0020] From the viewpoint of increasing the band gap and improving the TCR, the diameter of the carbon nanotube is preferably between 0.6 and 1.5 nm, more preferably between 0.6 and 1.2 nm, and even more preferably between 0.7 and 1.1 nm. In one embodiment, a diameter of 1 nm or less may be particularly preferable. If the diameter is 0.6 nm or more, the production of the carbon nanotube is easier. If the diameter is 1.5 nm or less, the band gap can be easily maintained within an appropriate range, and a high TCR can be obtained.
[0021] In this specification, the diameter of the carbon nanotube means that the diameter of about 50 points of the carbon nanotube on the substrate is measured using an atomic force microscope (AFM), and 60% or more, preferably 70% or more, in some cases more preferably 80% or more, and more preferably 100% of the diameters are within the range of 0.6 to 1.5 nm. Preferably, 60% or more, preferably 70% or more, in some cases more preferably 80% or more, and more preferably 100% of the diameters are within the range of 0.6 to 1.2 nm, and even more preferably 0.7 to 1.1 nm. In one embodiment, 60% or more, preferably 70% or more, in some cases more preferably 80% or more, and more preferably 100% of the diameters are within the range of 0.6 to 1 nm.
[0022] The length of the carbon nanotubes is preferably between 100 nm and 5 μm because they are easily dispersed and have excellent coating properties. From the viewpoint of the electrical conductivity of the carbon nanotubes, the length is preferably 100 nm or more. If the length is 5 μm or less, aggregation on the substrate is easily suppressed. The length of the carbon nanotubes is more preferably 500 nm to 3 μm, and further preferably 700 nm to 1.5 μm.
[0023] In this specification, the length of carbon nanotubes means that at least 60%, preferably at least 70%, in some cases more preferably at least 80%, and more preferably 100% of the length distribution of carbon nanotubes is within the range of 100 nm to 5 μm, as determined by observing and counting at least 50 tubes using an atomic force microscope (AFM). Preferably, at least 60%, preferably at least 70%, in some cases more preferably at least 80%, and more preferably 100% of the length is within the range of 500 nm to 3 μm. More preferably, at least 60%, preferably at least 70%, in some cases more preferably at least 80%, and more preferably 100% of the length is within the range of 700 nm to 1.5 μm.
[0024] When the diameter and length of the carbon nanotube are within the above ranges, the effect of semiconductivity becomes large and a large current value can be obtained, so that a high TCR value is likely to be obtained when used in an infrared sensor.
[0025] The thickness of the carbon nanotube layer is not particularly limited, but is, for example, 1 nm or more, for example, several nm to 100 μm, preferably 10 nm to 10 μm, and in one embodiment, more preferably in the range of 50 nm to 10 μm.
[0026] The content of semiconducting carbon nanotubes, preferably semiconducting single-walled carbon nanotubes, in the carbon nanotubes is generally more than 66% by mass, preferably 67% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more (including 100% by mass).
[0027] In the infrared sensor of this embodiment, the distance between the electrodes is preferably 1 μm to 500 μm, and more preferably 5 to 200 μm for miniaturization. If it is 5 μm or more, even if it contains a small amount of metallic carbon nanotubes, it is possible to suppress the deterioration of the TCR characteristics. Also, if it is 500 μm or less, it is advantageous for application to an image sensor by forming a two-dimensional array.
[0028] In the multiple carbon nanotubes connecting the first electrode and the second electrode, the number of carbon nanotubes between the electrodes (the number density of the carbon nanotubes in the carbon nanotube layer (3)) is 1 / μm 2 ~1000 lines / μm 2 It is preferable that the number of fibers is 10 / μm. 2 ~500 lines / μm 2 More preferably, the number of fibers is 50 / μm. 2 ~300 lines / μm 2 In one embodiment, the number of fibers / μm is preferably 10. 2 ~100 lines / μm 2 In some cases, it may be preferable to have 1 line / μm. 2If the density is smaller than 1000 / μm, it is difficult to form a conductive path. 2 If the thickness is less than this, even if a small amount of metallic carbon nanotubes are contained, the deterioration of the TCR characteristics is easily suppressed. The number of carbon nanotubes can be calculated, for example, by measuring the number of carbon nanotubes per area using an AFM at 10 random points (each of which is an area of 1 μm × 1 μm) on the carbon nanotube layer and averaging the results.
[0029] The substrate, electrodes, and other structures may be as described below.
[0030] An infrared sensor including carbon nanotubes as described above can be manufactured, for example, by a method including a cutting / dispersing step and a separation step of carbon nanotubes using a nonionic surfactant as described below, but it may also be manufactured using other methods.
[0031] An example of a method for manufacturing an infrared sensor according to an embodiment of the present invention will now be described in detail.
[0032] The carbon nanotubes may be heat-treated in an inert atmosphere or vacuum to remove surface functional groups, impurities such as amorphous carbon, catalysts, etc. The heat treatment temperature can be appropriately selected, but is preferably 800 to 2000°C, more preferably 800 to 1200°C.
[0033] The nonionic surfactant can be appropriately selected, but it is preferable to use one or more nonionic surfactants composed of a non-ionized hydrophilic portion and a hydrophobic portion such as an alkyl chain, such as a nonionic surfactant having a polyethylene glycol structure represented by polyoxyethylene alkyl ether, or an alkyl glucoside nonionic surfactant. As such a nonionic surfactant, a polyoxyethylene alkyl ether represented by formula (1) is preferably used. In addition, the alkyl portion may contain one or more unsaturated bonds.
[0034] Cn H 2n+1 (OCH 2 CH 2 ) m OH (1) (In the formula, n is preferably 12 to 18, and m is 10 to 100, preferably 20 to 100.)
[0035] In particular, nonionic surfactants defined as polyoxyethylene (n) alkyl ethers (n is 20 to 100, alkyl chain length is C12 to C18), such as polyoxyethylene (23) lauryl ether, polyoxyethylene (20) cetyl ether, polyoxyethylene (20) stearyl ether, polyoxyethylene (10) oleyl ether, polyoxyethylene (10) cetyl ether, polyoxyethylene (10) stearyl ether, polyoxyethylene (20) oleyl ether, and polyoxyethylene (100) stearyl ether, are more preferred. In addition, N,N-bis[3-(D-gluconamido)propyl]deoxycholamide, n-dodecyl β-D-maltoside, octyl β-D-glucopyranoside, and digitonin can also be used.
[0036] As a nonionic surfactant, polyoxyethylene sorbitan monostearate (molecular formula: C 64 H 126 O 26 , product name: Tween 60, manufactured by Sigma-Aldrich Co., Ltd., etc.), polyoxyethylene sorbitan trioleate (molecular formula: C 24 H 44 O 6 , product name: Tween 85, manufactured by Sigma-Aldrich Co., Ltd., etc.), octylphenol ethoxylate (molecular formula: C 14 H 22 O(C 2 H 4 O) n , n=1 to 10, product name: Triton X-100, manufactured by Sigma-Aldrich Co., etc.), polyoxyethylene (40) isooctylphenyl ether (molecular formula: C 8 H 17 C 6 H 40 (CH 2 CH20 ) 40 H, product name: Triton X-405, manufactured by Sigma-Aldrich Co., etc.), poloxamer (molecular formula: C 5 H 10 O 2 , trade name: Pluronic, manufactured by Sigma-Aldrich Co., Ltd., etc.), polyvinylpyrrolidone (molecular formula: (C 6 H 9 NO) n , n=5 to 100, manufactured by Sigma-Aldrich Co., etc.) can also be used.
[0037] The molecular length of the nonionic surfactant is preferably 5 to 100 nm, more preferably 10 to 100 nm, and even more preferably 10 to 50 nm. If it is 5 nm or more, particularly 10 nm or more, after the dispersion liquid is applied onto the electrode (including the region between electrode 1 and electrode 2), the distance between the carbon nanotubes can be appropriately maintained, and aggregation can be easily suppressed. Also, if it is 100 nm or less, it is preferable from the viewpoint of constructing a network structure.
[0038] The method for obtaining the dispersion solution is not particularly limited, and a conventionally known method can be applied. For example, a carbon nanotube mixture, a dispersion medium, and a nonionic surfactant are mixed to prepare a solution containing carbon nanotubes, and the solution is ultrasonically treated to disperse the carbon nanotubes, thereby preparing a carbon nanotube dispersion liquid (micelle dispersion solution). The dispersion medium is not particularly limited as long as it is a solvent that can disperse and suspend the carbon nanotubes during the separation process, and for example, water, heavy water, an organic solvent, an ionic liquid, or a mixture thereof can be used, but water and heavy water are preferred. In addition to or instead of the ultrasonic treatment, a carbon nanotube dispersion method using mechanical shearing force may be used. Mechanical shearing may be performed in the gas phase. It is preferable that the carbon nanotubes are isolated in the micellar dispersion aqueous solution of the carbon nanotubes and the nonionic surfactant. Therefore, if necessary, ultracentrifugation treatment may be used to remove bundles, amorphous carbon, impurity catalysts, etc. During the dispersion treatment, the carbon nanotubes can be cut, and the length can be controlled by changing the carbon nanotube crushing conditions, ultrasonic output, ultrasonic treatment time, etc. For example, the aggregate size can be controlled by crushing untreated carbon nanotubes with tweezers, a ball mill, or the like. After these treatments, the length can be controlled to 100 nm to 5 μm by using an ultrasonic homogenizer at an output of 40 to 600 W, sometimes 100 to 550 W, 20 to 100 KHz, and a treatment time of 1 to 5 hours, preferably up to 3 hours. If the treatment time is shorter than 1 hour, the nanotubes may hardly disperse depending on the conditions, and may remain almost at their original length. From the viewpoint of shortening the dispersion treatment time and reducing costs, 3 hours or less is preferable. This embodiment may also have the advantage that the cutting can be easily adjusted by using a nonionic surfactant. In addition, the infrared sensor according to this embodiment, which is manufactured using carbon nanotubes prepared by a method using a nonionic surfactant, also has the advantage that it does not contain an ionic surfactant, which is difficult to remove.
[0039] By dispersing and cutting the carbon nanotubes, surface functional groups are generated on the surface or ends of the carbon nanotubes. The functional groups generated include carboxyl groups, carbonyl groups, hydroxyl groups, etc. In the case of treatment in a liquid phase, carboxyl groups and hydroxyl groups are generated, and in the case of treatment in a gas phase, carbonyl groups are generated.
[0040] The concentration of the surfactant in the liquid containing the heavy water or water and the nonionic surfactant is preferably the critical micelle concentration to 10% by mass, more preferably the critical micelle concentration to 3% by mass. If it is below the critical micelle concentration, it is not preferable because it cannot be dispersed. If it is below 10% by mass, it is possible to apply carbon nanotubes with a sufficient density while reducing the amount of surfactant after separation. In this specification, the critical micelle concentration (CMC) refers to the concentration at which the surface tension is inverted when the concentration of the surfactant aqueous solution is changed and measured at a constant temperature using a surface tensiometer such as a Wilhelmy surface tensiometer. In this specification, the "critical micelle concentration" is a value at atmospheric pressure and 25°C.
[0041] The concentration of carbon nanotubes in the cutting and dispersion process (weight of carbon nanotubes / (total weight of dispersion medium and surfactant)×100) is not particularly limited, but can be, for example, 0.0003 to 10 mass%, preferably 0.001 to 3 mass%, and more preferably 0.003 to 0.3 mass%.
[0042] The dispersion obtained through the above-mentioned cutting and dispersion step may be used as it is in the separation step described below, or may be subjected to a step of concentration, dilution, or the like prior to the separation step.
[0043] Carbon nanotubes can be separated, for example, by an electric field induced layer formation method (ELF method: see, for example, K.Ihara et al. J.Phys.Chem.C.2011,115,22827-22832, Japanese Patent No. 5717233, which are incorporated herein by reference). An example of a separation method using the ELF method will be described. Carbon nanotubes, preferably single-walled carbon nanotubes, are dispersed in a nonionic surfactant, and the dispersion is placed in a vertical separation device, and a voltage is applied to electrodes arranged above and below, to separate the nanotubes by carrier-free electrophoresis. The mechanism of separation can be estimated as follows. When carbon nanotubes are dispersed in a nonionic surfactant, the micelles of semiconducting carbon nanotubes have a negative zeta potential, while the micelles of metallic carbon nanotubes have a zeta potential of the opposite sign (positive) (in recent years, it has been considered that they have a slightly negative zeta potential or are almost uncharged). Therefore, when an electric field is applied to the carbon nanotube dispersion, the semiconducting carbon nanotube micelles electrophores toward the anode (+) and the metallic carbon nanotube micelles electrophores toward the cathode (-) due to the effect of the difference in zeta potential. Finally, a layer in which the semiconducting carbon nanotubes are concentrated near the anode and a layer in which the metallic carbon nanotubes are concentrated near the cathode are formed in the separation tank. The voltage for separation can be appropriately set in consideration of the composition of the dispersion medium and the charge amount of the carbon nanotubes, and is preferably 1V or more and 200V or less, and more preferably 10V or more and 200V or less. From the viewpoint of shortening the time of the separation process, 100V or more is preferable. Also, from the viewpoint of suppressing the generation of bubbles during separation and maintaining separation efficiency, 200V or less is preferable. The purity of the separation is improved by repeating the separation. The dispersion after separation may be reset to the initial concentration and the same separation operation may be performed. This can further increase the purity.
[0044] The above-mentioned carbon nanotube dispersion / cutting step and separation step can provide a dispersion liquid in which semiconducting carbon nanotubes having a desired diameter and length are concentrated. In this specification, the carbon nanotube dispersion liquid in which semiconducting carbon nanotubes are concentrated may be referred to as a "semiconducting carbon nanotube dispersion liquid". The semiconducting carbon nanotube dispersion liquid obtained by the separation step means a dispersion liquid containing semiconducting carbon nanotubes generally more than 66% by mass, preferably 67% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, more preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more (the upper limit may be 100% by mass) of the total amount of carbon nanotubes. The tendency of separation of metallic and semiconducting carbon nanotubes can be analyzed by microscopic Raman spectroscopy and ultraviolet-visible-near infrared absorptiometry.
[0045] After the above-mentioned carbon nanotube dispersion / cutting step and before the separation step, a centrifugation treatment may be performed to remove bundles, amorphous carbon, metal impurities, etc. from the carbon nanotube dispersion liquid. The centrifugal acceleration can be appropriately adjusted, but is preferably 10,000×g to 500,000×g, more preferably 50,000×g to 300,000×g, and may be 100,000×g to 300,000×g in some cases. The centrifugation time is preferably 0.5 hours to 12 hours, more preferably 1 to 3 hours. The centrifugation temperature can be appropriately adjusted, but is preferably 4°C to room temperature, more preferably 10°C to room temperature.
[0046] In some embodiments, it may be preferable not to perform ultracentrifugation. In particular, in an embodiment in which the dispersion liquid containing carbon nanotubes contains a nonionic surfactant, particularly a nonionic surfactant with a large molecular length, it is easy to suppress bundle formation, so there is an advantage in that it is possible to reduce process steps and cut costs by not performing ultracentrifugation.
[0047] The semiconducting carbon nanotube dispersion obtained by the above-mentioned process is applied onto a substrate, dried, and optionally heat-treated, to form a carbon nanotube layer.
[0048] The substrate may be one having at least an insulating or semiconducting surface on which elements are to be formed, but it is particularly preferable to use one having an insulating surface on which elements are to be formed. For example, Si, SiO 2 Si, SiO 2 , SiN, parylene, polymers, resins, plastics, etc. can be used, but are not limited to these.
[0049] The surfactant concentration of the carbon nanotube dispersion liquid after separation to be applied to a substrate can be appropriately controlled. The surfactant concentration of the carbon nanotube dispersion liquid when applied to a substrate is preferably the critical micelle concentration to about 5 mass%, more preferably 0.001 mass% to 3 mass%, and particularly preferably 0.01 mass% to 1 mass% in order to suppress re-aggregation after application.
[0050] The zeta potential of the semiconducting carbon nanotube dispersion is preferably +5 mV to -40 mV, more preferably +3 mV to -30 mV, and even more preferably +0 mV to -20 mV. If it is +5 mV or less, it is preferable because it means that the content of metallic carbon nanotubes is low. If it is more than -40 mV, separation is difficult in the first place. Here, the zeta potential of the semiconducting carbon nanotube dispersion is the zeta potential of the semiconducting carbon nanotube dispersion containing a nonionic surfactant and semiconducting carbon nanotube micelles obtained by, for example, the separation step by the ELF method described above.
[0051] In this specification, the zeta potential of the carbon nanotube dispersion liquid is a value measured by using an ELSZ device (Otsuka Electronics Co., Ltd.).
[0052] The method for applying the carbon nanotube dispersion onto the substrate is not particularly limited, and examples thereof include a dropping method, spin coating, printing, inkjet, spray coating, dip coating, etc. From the viewpoint of reducing the manufacturing cost of the infrared sensor, the printing method is preferred.
[0053] The surfactant and the solvent can be removed from the carbon nanotubes applied on the substrate by heat treatment. The temperature of the heat treatment can be appropriately set to a temperature equal to or higher than the decomposition temperature of the surfactant, and is preferably 150 to 400°C, and more preferably 200 to 400°C. A temperature of 200°C or higher is more preferable because it is easier to suppress the residue of the decomposed product of the surfactant. Also, a temperature of 400°C or lower is preferable because it is possible to suppress the deterioration of the substrate. Also, it is possible to suppress the decomposition and size change of the carbon nanotubes, the detachment of functional groups, and the like.
[0054] The first and second electrodes on the substrate can be made using gold, platinum, or titanium, either singly or in combination. The method for making the electrodes is not particularly limited, but examples include vapor deposition, sputtering, and printing. The thickness can be adjusted as appropriate, but is preferably 10 nm to 1 mm, and more preferably 50 nm to 1 μm. The dispersion liquid may be applied to a substrate on which electrodes have already been provided, or the electrodes may be made before or after heat treatment after applying the dispersion liquid.
[0055] If necessary, a protective film may be provided on the surface of the carbon nanotube layer. The protective film is preferably made of a material that is highly transparent in the infrared wavelength range to be detected. Examples of the material include acrylic resins such as PMMA and PMMA anisole, epoxy resins, and Teflon (registered trademark).
[0056] The infrared sensor according to this embodiment may be a single element, or may be an array in which a plurality of elements are arranged two-dimensionally, as used in an image sensor.
[0057] This application claims priority based on Japanese Patent Application No. 2019-012928, filed on January 29, 2019, the disclosure of which is incorporated herein in its entirety. EXAMPLES
[0058] The present invention will be illustrated in more detail below with reference to examples, but the present invention is not limited to these examples.
[0059] Example 1 (Process 1) 100 mg of single-walled carbon nanotubes (Meijo Nano Carbon Co., Ltd., EC1.0 (diameter: 1.1-1.5 nm (average diameter 1.2 nm)) were placed in a quartz boat and heat-treated in an electric furnace under a vacuum atmosphere. The heat treatment temperature was 900°C and the time was 2 hours. The weight after heat treatment was reduced to 80 mg, indicating that the surface functional groups and impurities had been removed. The obtained single-walled carbon nanotubes were crushed with tweezers, and 12 mg was immersed in 40 ml of a 1 wt% aqueous solution of surfactant (polyoxyethylene (100) stearyl ether) and fully submerged, and then ultrasonic dispersion treatment (BRANSON ADVAN CD-DIGITAL SONIFIER device (output: 50 W)) was performed for 3 hours. As a result, there were no carbon nanotube aggregates in the solution. Then, ultracentrifugation treatment was performed at 50,000 rpm, 10°C, and 60 minutes. This operation removed bundles and residual catalysts, etc., and a carbon nanotube dispersion liquid was obtained. At this time, the dispersion liquid was immersed in SiO 2 After applying the solution to a substrate and drying at 100°C, the nanotubes were observed with an atomic force microscope (AFM). As a result, it was found that 70% of the single-walled carbon nanotubes were in the range of 500nm to 1.5μm in length, with an average length of approximately 800nm. For comparison, when the nanotubes were dispersed under similar conditions using an ionic surfactant (sodium dodecyl sulfate, SDS), the average length was greater, reaching approximately 1.5μm or more.
[0060] (Process 2) The carbon nanotube dispersion was introduced into the separation device shown in FIG. 3. Here, water 8 (about 15 ml), carbon nanotube dispersion 9 (about 70 ml), and 2 wt% surfactant aqueous solution 10 (about 15 ml) were introduced from the inlet with the inner tube 11 closed, and then 2 wt% surfactant aqueous solution (about 20 ml) was also introduced into the inner tube 11. Then, the inner tube 11 was opened, resulting in a three-layer structure as shown in FIG. 3. By applying a voltage of 120 V, the semiconducting carbon nanotubes moved to the anode side. Meanwhile, the metallic carbon nanotubes moved to the cathode side. About 80 hours after the start of separation, the separation was completed cleanly. The separation process was carried out at room temperature (about 25° C.). When the carbon nanotube dispersion that had moved to the anode side was analyzed by optical absorption spectroscopy, it was found that the metallic carbon nanotube components had been removed. In addition, the Raman spectrum showed that 99 wt% was semiconducting carbon nanotubes. In this case, the diameter of the single-walled carbon nanotubes was most often about 1.2 nm (70% or more), and the average diameter was 1.2 nm.
[0061] The zeta potential of the resulting semiconducting carbon nanotube dispersion was measured using an ELSZ device (Otsuka Electronics Co., Ltd.) and found to be approximately -10 mV.
[0062] (Step 3) 100 nm SiO on silicon substrate 2A substrate coated with 1,2-dichlorophenyl ether was prepared. The substrate was immersed in acetone, isopropyl alcohol, and ultrapure water in that order, and then ultrasonically treated to clean the substrate. After drying with nitrogen, oxygen plasma treatment was performed for 3 minutes. The substrate was immersed in a 0.1% APTES aqueous solution for 30 minutes. After washing with water, it was dried at 105°C. A carbon nanotube dispersion liquid (approximately 0.1 ml) adjusted to a concentration of 0.7 wt% was dropped onto the obtained substrate, and after leaving it for 30 minutes, it was washed with ethanol and dried at 110°C. It was heated at 200°C in air to remove nonionic surfactants, etc. Then, gold was evaporated at two locations on the substrate with a thickness of 100 nm and an interval of 50 μm. The area between the electrodes on the obtained substrate was observed with an atomic force microscope (AFM) (Figure 2). It was found that single-walled carbon nanotubes with a diameter of about 1.1 to 1.5 nm (average diameter 1.2 nm) were dispersed in a net shape because the surfactant was removed. The average length calculated by AFM observation was 1000 nm (more than 70% of the carbon nanotubes were within the range of 0.8 to 1.2 μm). It was also found that the surrounding single-walled carbon nanotubes did not re-aggregate due to the long molecular length of the surfactant. Next, a PMMA anisole solution was applied between the electrodes to protect the carbon nanotubes between the electrodes, and then excess carbon nanotubes near the electrodes were removed by oxygen plasma treatment. The sample was then dried at 200°C for 1 hour.
[0063] The number of carbon nanotubes in the carbon nanotube layer 3 of the fabricated substrate was measured using an AFM, and was found to be approximately 200 / μm 2 It was.
[0064] (Step 4) FIG. 4 shows the change in resistance value when the temperature of the infrared sensor produced in step 3 is changed. The TCR value (dR / RdT) was approximately -3.3% / K at 300K. This value was found to be significantly higher than the -2% / K of Comparative Example 1 and the vanadium oxide that has been conventionally used. This is because most of the carbon nanotubes that make up the carbon nanotube layer are semiconducting carbon nanotubes with small diameters and large band gaps. In addition, the nonionic surfactant can be easily removed, and the surfactant's large size suppresses the formation of bundles, forming an isolated and dispersed carbon nanotube network.
[0065] Comparative Example 1 An infrared sensor was produced from a carbon nanotube dispersion liquid produced in the same manner as in step 1 of Example 1, without carrying out the separation step in step 2, in a process similar to step 3. The TCR value at this time was approximately -0.5% / K. The low TCR value is due to the large amount of metallic carbon nanotubes contained.
[0066] Example 2 An infrared sensor was produced using single-walled carbon nanotubes with a diameter of about 0.8 to 1.1 nm (average diameter 0.9 nm) at least 70% of which was made of single-walled carbon nanotubes with a diameter of about 0.8 to 1.1 nm (average diameter 0.9 nm) in the same process as steps 1 to 3 of Example 1, except that in step 1 of Example 1, carbon nanotubes with a small diameter were used as raw materials. FIG. 5 shows the change in resistance value when the temperature of the infrared sensor was changed. The TCR value (dR / RdT) was about -5.0% / K at 300K. This TCR value became larger because the diameter became smaller and the band gap became larger. This result shows that the TCR value can be controlled by changing the diameter of the carbon nanotubes.
[0067] Comparative Example 2 An infrared sensor was produced using single-walled carbon nanotubes with a diameter of about 1.6 to 1.9 nm (average diameter 1.8 nm) at least 70% of which were single-walled carbon nanotubes with a diameter of about 1.6 to 1.9 nm (average diameter 1.8 nm) in the same process as steps 1 to 3 of Example 1, except that carbon nanotubes with a large diameter of about 1.6 to 1.9 nm (average diameter 1.8 nm) were used as the raw material in step 1 of Example 1. The TCR value at this time was about -2.0% / K. This is because the band gap is small when the diameter is large.
[0068] Although the present invention has been described above with reference to the embodiments and examples, the present invention is not limited to the above-mentioned embodiments and examples. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention. [Explanation of symbols]
[0069] 1 Board 2 Electrode 1 (1st electrode) 3 Carbon nanotube film (carbon nanotube layer) 4 Electrode 2 (second electrode) 5 cathode 6 Anode 7 Inlet / Outlet 8 water 9 Carbon nanotube dispersion 10 Surfactant solution 11 Inner tube
Claims
1. A substrate; a first electrode on the substrate; a second electrode on the substrate and spaced apart from the first electrode; a carbon nanotube layer electrically connected to the first electrode and the second electrode; Equipped with A bolometer-type infrared sensor, wherein the carbon nanotube layer contains semiconducting carbon nanotubes in an amount of 67 mass% or more of the total amount of carbon nanotubes, and 60% or more (number ratio) of all carbon nanotubes contained in the carbon nanotube layer have diameters in the range of 0.6 to 1.5 nm and lengths in the range of 100 nm to 3 μm, and the carbon nanotube layer has a thickness of 1 nm to 100 μm.
2. 2. The bolometer type infrared sensor according to claim 1, wherein the inter-electrode distance between the first electrode and the second electrode is 10 μm to 500 μm.
3. The number density of the carbon nanotubes in the carbon nanotube layer is 1 / μm 2 ~1000 lines / μm 2 3. The bolometer type infrared sensor according to claim 1, wherein
4. The bolometer-type infrared sensor according to any one of claims 1 to 3, wherein the semiconducting carbon nanotube has at least one surface functional group selected from a carboxyl group, a carbonyl group, and a hydroxyl group on at least one of the surface and the end.
5. 5. The bolometer-type infrared sensor according to claim 1, wherein the carbon nanotube layer contains semiconducting carbon nanotubes in an amount of 90 mass % or more of the total amount of the carbon nanotubes.
6. A method for manufacturing a bolometer type infrared sensor, comprising the steps of: The bolometer type infrared sensor is A substrate; a first electrode on the substrate; a second electrode on the substrate and spaced apart from the first electrode; a carbon nanotube layer electrically connected to the first electrode and the second electrode; Equipped with A step of preparing a solution containing carbon nanotubes by mixing carbon nanotubes, a nonionic surfactant, and a dispersion medium; a step of dispersing and cutting the carbon nanotubes by subjecting the solution to a dispersion treatment to prepare a carbon nanotube dispersion; a step of subjecting the carbon nanotube dispersion to carrier-free electrophoresis to separate the semiconducting carbon nanotubes and the metallic carbon nanotubes, thereby preparing a semiconducting carbon nanotube dispersion containing the semiconducting carbon nanotubes; A step of connecting the first electrode and the second electrode with a carbon nanotube layer by the following sub-steps (a) to (c): (a) a sub-step of applying the semiconducting carbon nanotube dispersion onto a substrate; (b) a sub-step of heat-treating the substrate on which the semiconducting carbon nanotube dispersion liquid is applied; and (c) a sub-step of forming a first electrode and a second electrode on a substrate before the sub-step of applying the semiconducting carbon nanotube dispersion liquid onto a substrate, or before or after the sub-step of heat-treating the substrate on which the semiconducting carbon nanotube dispersion liquid has been applied. and The semiconducting carbon nanotube dispersion contains semiconducting carbon nanotubes in an amount of 67% by mass or more of the total amount of carbon nanotubes in the dispersion, 60% or more (ratio by number) of all carbon nanotubes in the semiconducting carbon nanotube dispersion liquid have a diameter in the range of 0.6 to 1.5 nm and a length in the range of 100 nm to 3 μm, The carbon nanotube layer has a thickness of 1 nm to 100 μm.
7. The method according to claim 6, wherein the zeta potential of the semiconducting carbon nanotube dispersion is +5 mV to −40 mV, and the zeta potential is a value measured using a semiconducting carbon nanotube dispersion comprising water, a nonionic surfactant represented by the following formula (1) having a critical micelle concentration of up to 5% by mass, and carbon nanotubes containing 67% by mass or more of semiconducting carbon nanotubes. C n H 2n+1 (OCH) 2 CH 2 ) m OH (1) (Wherein, n = 12 to 18, m = 10 to 100)
8. The method according to claim 6 or 7, wherein the semiconducting carbon nanotube dispersion liquid contains semiconducting carbon nanotubes in an amount of 90 mass % or more of the total amount of carbon nanotubes.
9. The method according to any one of claims 6 to 8, wherein the dispersion treatment is an ultrasonic dispersion treatment.
10. A bolometer type infrared sensor according to any one of claims 1 to 5, wherein the carbon nanotubes contain 80 mass% or more single-walled carbon nanotubes.
Citation Information
Patent Citations
Electroconductive composition and electroconductive composite
JP2010163568A
Method of manufacturing semiconductor device
JP2011166070A
Infrared light-receiving element
JP2015049207A
Method for separating nano-carbons and apparatus for separating nano-carbons
JP2017001919A
Method for separating nanocarbon material, separation device, and separated nanocarbon dispersion solution
WO2010150808A1